2019
DOI: 10.1590/0001-3765201920181264
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent training with different frequencies on body composition and physical fitness in obese children

Abstract: Introduction: The aim of the study was to compare the effects of ten-week multicomponent training with different exercise frequencies on body composition (BC) and physical fitness (PF) in overweight and obese young children. Methods: 40 children, aged 12-15 (14.77±1.49), were randomly selected and assigned to experimental groups to train three times/week (EG1) or two times/week (EG2) for 10 weeks and a CG group (no training program). Results: It was shown that experimental groups (EG1 and EG2) improved similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…After excluding 1080 records due to their irrelevance to the research question, 1657 were considered eligible for full‐text assessment (Figure 1). A total of 116 articles 24–139 describing 114 independent trials were included in this systematic review and meta‐analysis with 23 articles examining children or adolescents, 24–46 30 articles examining young adults, 47–76 38 articles examining middle‐aged adults,…”
Section: Resultsmentioning
confidence: 99%
“…After excluding 1080 records due to their irrelevance to the research question, 1657 were considered eligible for full‐text assessment (Figure 1). A total of 116 articles 24–139 describing 114 independent trials were included in this systematic review and meta‐analysis with 23 articles examining children or adolescents, 24–46 30 articles examining young adults, 47–76 38 articles examining middle‐aged adults,…”
Section: Resultsmentioning
confidence: 99%
“…A total of 23 RCTs were included in meta-regression analysis [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. The PRISMA flow diagram is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…An important limitation is the heterogeneity in CRF protocol tests and body fat assessment. Most of the RCTs used spirometry to determine oxygen consumption; though many others applied field-tests such as the 20-m Shuttle Run [17,22,24]. However, meta-regression analysis using more robust assessments showed higher variance explained and lower heterogeneity between results.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…Multicomponent exercise programs improve physical fitness in overweight and obese children regardless of exercise frequency [24]. Bogataj et al reported that highintensity intermittent exercise increased muscle strength and aerobic performance in girls [25].…”
Section: Discussionmentioning
confidence: 99%